Index funds : - McClatchy, Will (Wiley, 2003)
A comprehensive look into the world of index funds from the top name in the business. Index funds are a growing segment of the investing world, due in part to their higher average returns and a virtual certainty of achieving target index. An Insider's Guide to Index Funds fully describes the ins and outs of this investment tool that gives investors the benefit of individual stocks and lower costs associated with mutual funds. The scope of this guide includes everything from a description of various index funds to building a sensible fortfolio to saving on taxes to the risk associated with index funds. Seasoned veterans as well as novices will benefit from the depth of knowledge and proven advice that only Indexfunds.com can provide.